2012
DOI: 10.1177/0361684312454842
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Protective Paternalism for Men in Romantic and Work Contexts

Abstract: Behavioral prescription specifies how people ought to act. Five studies investigated prescription for men of protective paternalism, a particular form of benevolent sexism, depending on contextual and individual factors. In Studies 1 and 2, female participants prescribed for men more protective paternalistic behavior toward women in a romantic than in a work context. In Study 3, male participants prescribed the same level of protective paternalistic behavior as female participants did. Conversely, more gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
(92 reference statements)
1
39
0
Order By: Relevance
“…On the other hand, women tend to form relatively favorable impres sions of men who espouse benevolently sexist beliefs (Kilianski & Rudman, 1998), and they view at least some forms of benevolent sexism as appropriate in romantic contexts (Sarlet, Dumont, Delacollette, & Dardenne, 2012). For instance, many women expect their male romantic partners to convey protective paternalism toward them, and they may not view such treatment as sexist when it comes from a romantic partner (Sarlet et al, 2012). Thus, women have both positive and negative reactions to benevolent sexism.…”
Section: Women's Responses To Hostile and Benevolent Sexismmentioning
confidence: 99%
“…On the other hand, women tend to form relatively favorable impres sions of men who espouse benevolently sexist beliefs (Kilianski & Rudman, 1998), and they view at least some forms of benevolent sexism as appropriate in romantic contexts (Sarlet, Dumont, Delacollette, & Dardenne, 2012). For instance, many women expect their male romantic partners to convey protective paternalism toward them, and they may not view such treatment as sexist when it comes from a romantic partner (Sarlet et al, 2012). Thus, women have both positive and negative reactions to benevolent sexism.…”
Section: Women's Responses To Hostile and Benevolent Sexismmentioning
confidence: 99%
“…The protective attitudes associated with BS are identified as “sexist” because prior research has shown BS maintains men's societal advantages through emphasizing women's interpersonal qualities and importance in the relationship domain, reducing women's competence and ambition outside the home (e.g., Barreto, Ellemers, Piebinga, & Moya, ; Dardenne, Dumont, & Bollier, ; Sinclair, Huntsinger, Skorinko, & Hardin, ). Despite these costs, however, BS is perceived favorably by women and not typically seen as “sexist” (Barreto & Ellemers, ; Kilianski & Rudman, ; Sarlet, Dumont, Delacollette, & Dardenne, ). This is because BS fosters relationship benefits for both women and men: Women are revered for their relational competence, and receive protective, caring behavior from male partners who endorse BS (Overall, Sibley, & Tan, ), and men are able to secure satisfying relationships while also maintaining greater social power as the provider outside the home (Hammond & Overall, ; Sibley & Becker, ).…”
Section: Bs and Ideal Standards For Relationship Partnersmentioning
confidence: 99%
“…Critically, the warmth/trustworthiness expectations contained within BS are prescriptive in nature; women and men “ought to” and “should be” warm, sensitive, supportive, and loyal (Delacollette, Dumont, Sarlet, & Dardenne, ; Sarlet et al, ). Such prescriptions create strong boundaries of how men and women should and should not be or behave (Burgess & Borgida, ).…”
Section: Bs and Ideal Standards For Relationship Partnersmentioning
confidence: 99%
“…Indeed, previous research has demonstrated that women are more likely to accept a sexist restriction (e.g., the man should do all the driving on a road trip) when the restriction was made by a husband compared to a coworker (Moya et al, 2007). Furthermore, when queried on their expectations of how men should behave, women are more likely to prescribe benevolently sexist behaviors (e.g., "I expect a man to be protective towards me") for a romantic partner but not a coworker (Sarlet, Dumont, Delacollette, & Dardenne, 2012). Yet, women experience sexism from a variety of different types of perpetrators (Swim et al, 2001).…”
Section: Type Of Perpetratormentioning
confidence: 99%